'Sheds for Life': getting the balance right in delivering health promotion through Sheds in Ireland. (24th August 2020) - Bergin, Niamh; Richardson, Noel
Summary: Men with the poorest health outcomes are, paradoxically, the least likely to access health services or to engage with health promotion interventions. This has focused attention on developing gender-sensitive and strengths-based approaches to engage so-called 'hard-to-reach' men. Men's Sheds ('Sheds') are recognized as an alternative space in which to engage older and more marginalized groups of men in health. The aim of this study was to establish key principles that could align the ethos of Sheds with a national health promotion initiative ('Sheds for Life'; SFL) in terms of methods of engagement, programme content and models of delivery. Qualitative methods incorporating semi-structured interviews, focus groups and observations were conducted with men in Sheds ('Shedders'; n = 38), oversight/advisory groups ( n = 11) and partner organizations ( n = 8). The principles of grounded theory were used to inform data collection and analysis. Findings revealed a range of mediating factors in terms of how Shedders engage with or 'do' health that were grounded in a recognition of the health-enhancing 'essence' of Sheds and in 'making men's health men's business'. Key learnings arising from the process of engaging with Shedders included the importance of investing in relationships, establishing credibility and tailoring SFL programme content and delivery to individual Sheds. In terms of conceptualizing SFL, attention was drawn to the need for a coherent and formalized SFL strategy and 'rules of engagement', as well as a robust and sustainable system for implementation. This is the first study that informs a more systematic and formal approach to health promotion in Sheds.